2021
DOI: 10.1111/jac.12478
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the impact of future climate change on maize yield and water use efficiency in agro‐pastoral ecotone of Northwestern China

Abstract: Maize plays an important role in the Agro‐pastoral ecotone of Northwestern China (APENC), where highly sensitive to changes in climate conditions. However, little is reported on the impacts of climate change on crops in the region. In this study, we used Decision Support System for Agrotechnology Transfer model driven by future climate data from 20 general circulations models under two representative concentration pathways (RCPs: RCP4.5 and RCP8.5) from the Coupled Model Intercomparison Project Phase 5 (CMIP5)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 69 publications
(78 reference statements)
0
9
0
Order By: Relevance
“…There was an increase of 81–82% higher WUE in IR64 and 73–85% increase in IR 83376‐B‐B‐24–2 during wet season 2014 and 2015, respectively. Han et al (2021) also reported that high temperature has negative effect on WUE of maize. Higher [CO 2 ] levels will influence stomatal behaviour beneficially by reducing water loss through transpiration, thus increasing water use efficiency (Wassmann et al, 2009).…”
Section: Resultsmentioning
confidence: 96%
“…There was an increase of 81–82% higher WUE in IR64 and 73–85% increase in IR 83376‐B‐B‐24–2 during wet season 2014 and 2015, respectively. Han et al (2021) also reported that high temperature has negative effect on WUE of maize. Higher [CO 2 ] levels will influence stomatal behaviour beneficially by reducing water loss through transpiration, thus increasing water use efficiency (Wassmann et al, 2009).…”
Section: Resultsmentioning
confidence: 96%
“…A study in north-western China for the end of the 21st century predicted a decline under the four climate scenarios and more significantly under RCP 8.5. 37 The rising temperatures within 1 °C would not cause a significant effect but higher than that would lead to losses in maize yield by 11.3% with fertilization effects of CO 2 concentration and by 10.8% without the fertilization effect of CO 2 concentration. The elevated CO 2 has a positive impact on maize yield but the increasing temperatures offsets this positive impact.…”
Section: Discussionmentioning
confidence: 99%
“…The Yuyang District is located at 37.81 • -38.92 • N, 108.94 • -110.41 • E (Figure 1), Shaanxi Province, China, and covers a total area of~7000 km 2 . This area is part of the ecologically fragile transition zone between the desert-grassland area and the Loess Plateau region [13,[49][50][51][52]. The region has a semi-arid continental monsoon climate, with an average annual temperature of 8.4 • C and an average annual precipitation of 402 mm that gradually decreases from the southeast to northwest.…”
Section: Study Areamentioning
confidence: 99%